"Something Is Wrong Here": An Interview With Sarah Cox About Damming Canadian Rivers for Hydroelectricity. (February 2021) - Sheehan, Margaret
Only one-third of the world's rivers remain free flowing, and one million species face extinction. In the climate crisis, the race for "clean energy" is on. Over the last century, the Canadian government has built hundreds of hydropower dams and is pushing ahead with more big dams despite decades of science showing their irreversible and significant social, environmental, and economic harms. Canada markets its hydropower as "clean" and "renewable." In her book, Breaching the Peace: The Site C Dam and a Valley's Stand Against Big Hydro, journalist Sarah Cox documents the externalities caused by Canada's megadams and the ongoing struggle by indigenous people, farmers, and activists to stop one of the largest and most controversial dams located on the Peace River in British Columbia, Canada. Meg Sheehan, environmental attorney, interviewed Cox during the COVID-19 pandemic to get the story behind Canada's hydropower policy and how things can change.